Urachal Mucinous Cystic Tumor of Low Malignant Potential with Concurrent Sigmoid Colon Adenocarcinoma. (25th June 2019) - Brennan, Kelly; Johnson, Paul; Curtis, Heather; Arnason, Thomas
Abstract : Urachal mucinous tumors are rare neoplasms with behaviour that can range from relatively benign to malignancy that can spread distantly or throughout the peritoneum as pseudomyxoma peritonei or peritoneal carcinomatosis. Here we describe a unique case of urachal mucinous cystic tumor of low malignant potential confined to an intact cyst at the dome of the urinary bladder, without rupture or peritoneal spread. The urachal mucinous tumor was an incidental finding on a staging CT scan performed for sigmoid colon adenocarcinoma. We believe that this case illustrates a potential diagnostic pitfall which could have prognostic and therapeutic implications. Due to the intestinal phenotype of these neoplasms, a urachal tumor of low malignant potential could be mistaken for metastatic spread from a colonic adenocarcinoma in the rare situation such as this case, where the two neoplasms occur concurrently.